--If you grew up with George Washington - Gross, Ruth Belov; McCully, Emily Arnold (New York : Scholastic, 1993)
Tells what your life would be like if you had lived at the same time as George Washington.
4.1
K-3
Keywords: Washington, George, -- 1732-1799 -- Childhood and youth -- Juvenile literature; Washington, George, -- 1732-1799 -- Childhood and youth; Washington, George, -- 1732-1799.; Virginia -- Social life and customs -- To 1775 -- Juvenile literature; Virginia -- Social life and customs -- To 1775.; Virginia -- Social life and customs